E-money and card payment instruments affect money speed in Indonesia - Sitanggang, Romauli; Tiawon, Harin; Beatris, Diana (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
This comprehensive study is meticulously designed to thoroughly examine and elucidate the profound impact that electronic money, commonly referred to as e-money, along with various payment instruments that utilize cards, has on the dynamics of money circulation within the economic landscape of Indonesia. To achieve this objective, the research methodology employed in this investigation is a rigorous multiple linear regression analysis, which is conducted with the sophisticated statistical software known as EViews 9, and it is imperative to note that the type of data utilized in this research is categorized as secondary data. The secondary data, which has been meticulously gathered for the purposes of this analysis, has been sourced from reputable institutions, specifically the Central Statistics Agency and Bank Indonesia, both of which provide a wealth of information that has been systematically collected and organized for analytical scrutiny. The findings derived from this extensive study reveal that, whether examined in isolation or collectively, the total volume of electronic money currently in circulation, the quantity of Electronic Data Capture (EDC) machines operational in the market, and the various Card Payment Instruments (APMK) all exert a significant and positive influence on the overall money circulation within the Indonesian economy. Furthermore, this research contributes valuable insights into the transformative role that these modern financial instruments play in shaping monetary flows, thereby enhancing our understanding of contemporary financial practices in Indonesia. Ultimately, the implications of these findings underscore the necessity for stakeholders in the financial sector to recognize and adapt to the evolving landscape of digital payment mechanisms as they continue to permeate and redefine traditional notions of currency circulation.